Enhancement of the work function of indium tin oxide by surface modification using caesium fluoride - Whitcher, T.J.; Yeoh, K.H.; Ng, C.Y.B.; Talik, N.A.; Chua, C.L.; Woon, K.L.; Chanlek, N.; Nakajima, H.; Saisopa, T.; Songsiriritthigul, P.; Oswald, S.; Yap, B.K. (Institute of Physics, 2013)
The work function of indium tin oxide (ITO) was modified using caesium fluoride (CsF). Various concentrations of CsF was spin-coated on top of ITO and baked while the residual CsF was washed away with DI water. The work function of all the ITO samples was measured using ultraviolet photoelectron spectroscopy and it was found that the work function of ITO reaches as high as 5.75 eV. The work function rapidly increases with small concentrations of CsF solution and then decreases for higher concentrations. Using atomic force microscopy and x-ray photoelectron spectroscopy, the cause was determined to be the change in surface roughness and the oxygen concentration, with the former having a much greater influence on the work function than the latter. The current density of ITO/poly(vinylcarbazole)/Al hole-only devices using the modified ITO increases by more than seven orders of magnitude compared with the control device.